2015
DOI: 10.1016/j.annemergmed.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Methylene Blue in an Experimental Model of Calcium Channel Blocker–Induced Shock

Abstract: BACKGROUND Calcium channel blocker poisonings account for a substantial number of reported deaths from cardiovascular drugs. While supportive care is the mainstay of treatment, experimental therapies such as high dose insulin-euglycemia and lipid emulsion have been studied in animal models and used in humans. In the most severe cases even aggressive care is inadequate and deaths occur. In both experimental models and clinical cases of vasodilatory shock, methylene blue improves hemodynamic measures. Methylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…However, there does not seem to be a contraindication to giving them concurrently as insulin has shown benefit in some circumstances, 141 and LRT has been shown better in others 63 , 196 . Another alternative is methylene blue, which will increase the median survival time for calcium channel blocker toxicity by increasing pulse rate and mean arterial pressure 197 . Other reviews have covered the topic well, with the conclusion that 1–2 mg/kg of 1% methylene blue can be beneficial in toxin‐induced shock as an adjuvant to vasopressors 198 …”
Section: Part Iv: Next‐generation Lipid Therapymentioning
confidence: 99%
“…However, there does not seem to be a contraindication to giving them concurrently as insulin has shown benefit in some circumstances, 141 and LRT has been shown better in others 63 , 196 . Another alternative is methylene blue, which will increase the median survival time for calcium channel blocker toxicity by increasing pulse rate and mean arterial pressure 197 . Other reviews have covered the topic well, with the conclusion that 1–2 mg/kg of 1% methylene blue can be beneficial in toxin‐induced shock as an adjuvant to vasopressors 198 …”
Section: Part Iv: Next‐generation Lipid Therapymentioning
confidence: 99%
“…The human reports primarily describe the successful use of methylene blue in vasodilatory shock caused by dihydropyridine calcium channel blockers, though successful treatment of shock from quetiapine [9] and valsartan [12] with methylene blue has also been described. A recently published animal study found significant increases in pulse, mean arterial pressure, and median survival time after administration of methylene blue in an experimental model of amlodipine-induced shock in rats [11]. Upon review of the human cases, however, we find no cases where hemodynamic data from invasive monitoring was available during the administration of methylene blue to more accurately describe its physiologic effects in humans with drug-induced vasodilatory shock.…”
Section: Introductionmentioning
confidence: 77%
“…Increases in systemic vascular resistance and mean arterial pressure have been consistently described following methylene blue administration for shock due to non-poisoning causes, including vasoplegic syndrome after coronary artery bypass surgery [4] and sepsis [5][6][7]. Methylene blue, from a mechanistic standpoint, is an attractive therapy for drug-induced vasodilatory shock, though published literature includes only a small number of human case reports and animal studies [8][9][10][11]. The human reports primarily describe the successful use of methylene blue in vasodilatory shock caused by dihydropyridine calcium channel blockers, though successful treatment of shock from quetiapine [9] and valsartan [12] with methylene blue has also been described.…”
Section: Introductionmentioning
confidence: 99%
“…Limited evidence also supports the use of methylene blue in the treatment of shock from calcium channel antagonists [124,125]. In a single case report, methylene blue was successfully used in a mixed atenolol and amlodipine ingestion [126].…”
Section: Vasoactive Agentsmentioning
confidence: 99%